Fitossociologia em sub-bosque de Eucalyptus paniculata Smith da Lagoa do Piauzinho, Ipaba, Minas Gerais, Brasil (Lundiana: International Journal of Biodiversity, 2011)
Eucalyptus is a common element in the landscapes of southeastern Brazil, with economic and forestry value, and is also the target of several controversies. In this study, floristic and phytosociologic parameters are described for the understory of an Eucalyptus paniculata wood located at Lagoa do Piauzinho, municipality of Ipaba, in the Brazilian state of Minas Gerais. Sampling was done between April and May 2006, for the analysis of floristic composition, species aggregation, and horizontal, diametric and vertical structure. One hundred and one individuals belonging to 22 species of 16 families were sampled in two parcels. The most abundant species were Apuleia leiocarpa, Lecythis lurida and Casearia sp. 2. The floristic diversity of the area was low compared to those found in other similar studies. The E. paniculata wood offered adequate conditions for the development of the different successional stages, with some latesuccession species starting to appear and to colonize the understory.